2016
DOI: 10.15587/2312-8372.2016.81015
|View full text |Cite
|
Sign up to set email alerts
|

Research of chromium (VI) ion adsorption by montmorillonite modified by cationic surfactants

Abstract: Zhdanyuk N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The lid of the structural packets of the mineral occurred as a result of the replacement of exchange cations in the interlayer space of montmorillonite with large volume HDTMA molecules [8][9][10]. Studies conducted in [3] showed that increasing the ratio of CEC/surfactants to 2 allows to increase the interplanar distance to 2.25 nm.…”
Section: Research Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lid of the structural packets of the mineral occurred as a result of the replacement of exchange cations in the interlayer space of montmorillonite with large volume HDTMA molecules [8][9][10]. Studies conducted in [3] showed that increasing the ratio of CEC/surfactants to 2 allows to increase the interplanar distance to 2.25 nm.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Studies confirm that the purification of aqueous media by synthesized OMT1 and OMT2 composites from Cr(VI) ions reached the maximum permissible concentration (MPC), which is 0.05 mg/dm 3 [14].…”
Section: Issn 2664-9969mentioning
confidence: 92%
See 2 more Smart Citations